Proposal to strengthen educational building ancient II-MOP. Venezuela (Gaceta Técnica, 2017)
This article presents the study of structural reinforcement for a building of educational use, known as "Old Type II". The school was built before the creation of the Venezuelan Seismoresistant Covenin 1756. The results of the structural analysis showed insufficient responsiveness to service requests, high vulnerability to seismic action and deficiencies in the quantity and distribution of reinforcing steel. For this reason, the reinforcement of the superstructure was proposed by the construction of panel walls, verifying their action on the existing piloting system. For the modeling, the values of resistance of the concrete obtained in the destructive tests made by the materials laboratory of the School of Civil Engineering of the Universidad Centroccidental Lisandro Alvarado and the soil parameters from the geotechnical study were used.
Keywords: reinforcement; structure; adequacy; vulnerability; soil; Venezuela